Clinical And Genetic and Immuno-Microbiological Aspects of Ichthyosis and Methods of Pathogen Etic Treatment - Eshniyazov Mahmudbek Maksudovich (Central Asian Journal of Medical and Natural Science, 2023)
This article is intended to identify a hereditary skin disease in which the process of keratinization of the epidermis is disturbed. The skin dries up and peels off, and in severe cases of the disease, the skin begins to appear on the skin. Often, ichthyosis appears in early childhood and is inherited from parents.